Stereodivergent Synthesis of rac-cis- and rac-trans-4-Hydroxyphosphopipecolic Acids - Morales-Solís, Juan Carlos; Ordóñez, Mario; Argüello-Velasco, Rubén Oswaldo; Viveros-Ceballos, José Luis; Labastida-Galván, Victoria (Synthesis, 2024)
We report herein the first stereodivergent synthesis of rac-cis- and rac-trans-4-hydroxyphosphopipecolic acids. The main feature of this methodology is the controlled cis or trans reduction of 4-oxophosphopipecolates by exclusively varying the size of the hydride reagents. Thus, a small hydride reagent (NaBH4) adds selectively from the axial side of the carbonyl group to give the equatorial hydroxyl group (cis-product), whereas a bulky hydride reagent such as LiBH(sec-Bu)3 (L-Selectride®) preferentially attacks from the equatorial side, giving the hydroxyl group in the axial position (trans-product). In the last step, hydrolysis of the diethyl phosphonate and ethyl phenylphosphinate groups with bromotrimethylsilane, followed by methanolysis, led to the target compounds.
Keywords: stereodivergent synthesis; diastereoselective reduction; 4-hydroxyphosphopipecolic acid; heterocyclic α-aminophosphonic acids; heterocyclic α-aminophenylphosphinic acids